2020
DOI: 10.3390/rs12233913
|View full text |Cite
|
Sign up to set email alerts
|

Observing Snow Cover and Water Resource Changes in the High Mountain Asia Region in Comparison with Global Mountain Trends over 2000–2018

Abstract: The quantification of snow cover changes and of the related water resources in mountain areas has a key role for understanding the impact on several sectors such as ecosystem services, tourism and energy production. By using NASA-Moderate Resolution Imaging Spectroradiometer (MODIS) images from 2000 to 2018, this study analyzes changes in snow cover in the High Mountain Asia region and compares them with global mountain areas. Globally, snow cover extent and duration are declining with significant trends in ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 80 publications
(112 reference statements)
4
6
0
Order By: Relevance
“…Nevertheless, we would like to stress that our findings align well with recent studies examining snow cover dynamics over continental to hemispherical scales but over much shorter timescales 29,30,[33][34][35] . In particular, the observed high interannual variability often impeding clear long-term trends is also observed by smaller-scale regional studies, and mainly linked to elevation, monsoon-influence and heterogeneously changing temperature and precipitation patterns 28,[36][37][38] .…”
Section: Resultssupporting
confidence: 91%
“…Nevertheless, we would like to stress that our findings align well with recent studies examining snow cover dynamics over continental to hemispherical scales but over much shorter timescales 29,30,[33][34][35] . In particular, the observed high interannual variability often impeding clear long-term trends is also observed by smaller-scale regional studies, and mainly linked to elevation, monsoon-influence and heterogeneously changing temperature and precipitation patterns 28,[36][37][38] .…”
Section: Resultssupporting
confidence: 91%
“…Haag et al (2019) reported a slightly positive trend in summer, winter and autumn precipitation for the Tien Shan that might influence the close-to-zero and slightly positive mass balances at the southern margin of the Tien Shan. This is in agreement with the increase of snow cover fraction reported in Notarnicola (2020). Therefore, the main driver seems to be precipitation and snow cover in spring and summer (Fig.…”
Section: Analysis Ii: Era5 Dataset and Mb Hugonnetetalsupporting
confidence: 92%
“…8, 7). This is in line with heterogeneous and sharply contrasting snow cover changes reported by Notarnicola (2020), showing a positive snow cover change matching the location of the positive mass balance anomaly in Barandun et al (2021). The neighbouring negative mass balance anomaly in the Central Tien Shan shows predominantly a spring and air temperature importance, where a sharp decrease in snow cover duration was reported (Notarnicola, 2020).…”
Section: Analysis I: Har Dataset and Mb Barandunetalsupporting
confidence: 82%
See 1 more Smart Citation
“…Snow cover (SC) and its extent is a widely used parameter to characterize the spatiotemporal distribution of these glaciers since it serves as a conduit between surface processes and the atmosphere over it. In fact, observational studies (Notarnicola, 2020) and future projections (Lalande et al., 2021) report that approximately 86% of HMA areal extent exhibit negative trends in SC due to climate change.…”
Section: Introductionmentioning
confidence: 99%